Clinical Relevance of Tumor Markers in Genitourinary Cancer Diagnosis and Treatment - a Literature Review - Roś, Bartosz; Kowalewski, Wojciech; Siekaniec, Katarzyna; Jakubowicz, Magdalena; Kuchenbeker, Natalia; Dojs, Adriana; Mierzwińska-Mucha, Julia (Journal of Education, Health and Sport, 2025)
Introduction and purpose: In recent years, the number of patients diagnosed with genitourinary cancers, including prostate cancer, kidney cancer, bladder cancer, and testicular cancer, has been increasing. Tumor markers—substances pathologically produced in the body during cancer development—ensure rapid diagnosis and subsequent treatment monitoring. A brief description of the state of knowledge: In the case of prostate cancer, the primary tumor marker is prostate-specific antigen (PSA). It demonstrates high sensitivity but low specificity, and various parameters related to this marker allow accurate diagnosis or help avoid unnecessary biopsies. Markers associated with renal cell carcinoma (such as carbonic anhydrase IX and Ki67) have diagnostic potential but are not routinely used. Traditional testicular cancer markers (alpha-fetoprotein, human chorionic gonadotropin, lactate dehydrogenase) are routinely used to assess disease stage and prognosis. Bladder cancer markers (e.g., bladder tumor antigen, nuclear matrix protein 22) have varying levels of sensitivity and specificity, and unfortunately, none can replace cystoscopy. Summary: Each of the diseases described has tumor markers of clinical significance; however, none of them is fully reliable, with the most common limitations being low specificity and the possibility of false-positive or false-negative results. Further research on new markers, including genetic and epigenetic ones, is needed to reduce treatment costs and enable more precise diagnosis of these diseases.